Reading texts between generations: a proposal concerning theological engagement with genetic research - Muers, Rachel (Scottish journal of theology, 2004)
The issue of the ethical status of future generations is significant in debates about research in human genetics, but key (non-theological) statements on the subject, such as the UNESCO Declaration on Human Rights and the Human Genome, reflect a failure to think of future persons as located within communities of ethical reflection and interpretation. I draw on recent work in the philosophy of conservation biology to explore this failure, and argue that a major contribution of theology to ethical reflection on genetic research would be through discussion of ways of reading, transmitting and interpreting texts.